'Close but not too close' – experiences of science-policy bridging in three international advisory organizations. Issue 1 (2nd January 2023) - De Donà, Matteo; Linke, Sebastian
ABSTRACT: The role of science in environmental decision-making calls for an improved understanding of how scientific advice can best inform policy. Policy-relevant science is trapped in the conundrum of being close to policy and politics while trying not to become too close, to avoid politicization. We investigate this dilemma in three scientific advisory organizations: the International Council for the Exploration of the Sea (ICES), the Intergovernmental Panel on Climate Change (IPCC), and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). Comparing marine, climate, and biodiversity governance at the international level, we reveal how the science-policy interface is understood and arranged in the institutional designs of these organizations. While they are all mandated to be policy-relevant, they aim to provide a neutral space for science that is not overtly impacted by politics. Our analysis reveals key differences in science-policy interactions regarding four issues: mandate ; science-policy separation; politicization of advisory science; and knowledge inclusion . After discussing how these dimensions exhibit challenges connected to the 'proximity vs. distance' dilemma, we formulate an ideal-typical continuum comprising the following arrangements: a clear-cut boundary, a boundary zone, a fuzzy boundary. Based on this three-tiered model, we argue for a non-dichotomous understanding of science-policy relationships.